Affective Economy: A Theoretical Outline - Michele Filippo Fontefrancesco (Encyclopedia, 2023)
The affective economy is a concept that emerged within the field of social sciences, focusing on the interplay between emotions, affects, and economic processes. It explores how emotions and affective experiences shape economic practices, consumption patterns, and the production of goods and services. In the affective economy framework, emotions are seen as not merely individual but deeply embedded in social and political contexts, shaping and being shaped by social structures and power dynamics. The affective economy emphasizes how emotions circulate and contribute to the construction and maintenance of social orders, impacting economic actions. It acknowledges the profound impact of emotions and affects on economic behavior. Thus, this concept sheds light on the intricate relationship between emotions and economic processes, demonstrating how affective experiences influence consumption, production, labor, financial decisions, and the overall dynamics of the market economy. It emphasizes the need for a more nuanced understanding of human behavior in economic contexts, recognizing the significance of emotions and affective responses as integral components of economic activities. This concept is connected to notions of dwelling, topophilia, and affective atmospheres, providing insights into the complexities of economic transactions in diverse cultural contexts.